Comparison of new psychiatric diagnoses among Finnish children and adolescents before and during the COVID-19 pandemic: A nationwide register-based study - Gyllenberg David; Bastola Kalpana; Yunus Wan Mohd Azam Wan Mohd; Mishina Kaisa; Liukko Emmi; Kääriälä Antti; Sourander Andre (PUBLIC LIBRARY SCIENCE, 2026)
Background
Coronavirus Disease 2019 (COVID-19) restrictions decreased the use of specialist psychiatric services for children and adolescents in spring 2020. However, little is known about the pattern once restrictions eased. We compared new psychiatric diagnoses by specialist services during pandemic and pre-pandemic periods.
Methods and findings
This national register study focused on all Finnish residents aged 0 to 17 years from January 2017 to September 2021 (approximately 1 million a year). The outcomes were new monthly diagnoses for psychiatric or neurodevelopmental disorders in specialist services. These were analyzed by sex, age, home location, and diagnostic groups. The numbers of new diagnoses from March 2020 were compared to predictive models based on previous years. The predicted and observed levels in March to May 2020 showed no significant differences, but the overall difference was 18.5% (95% confidence interval 12.0 to 25.9) higher than predicted in June 2020 to September 2021, with 3,821 more patients diagnosed than anticipated. During this period, the largest increases were among females (33.4%, 23.4 to 45.2), adolescents (34.4%, 25.0 to 45.3), and those living in areas with the highest COVID-19 morbidity (29.9%, 21.2 to 39.8). The largest increases by diagnostic groups were found for eating disorders (27.4%, 8.0 to 55.3), depression and anxiety (21.0%, 12.1 to 51.9), and neurodevelopmental disorders (9.6%, 3.0 to 17.0), but psychotic and bipolar disorders and conduct and oppositional disorders showed no significant differences and self-harm (−28.6, −41.5 to −8.2) and substance use disorders (−15.5, −26.4 to −0.7) decreased in this period. The main limitation is that data from specialist services do not allow to draw conclusions about those not seeking help.
Conclusions
Following the first pandemic phase, new psychiatric diagnoses in children and adolescents increased by nearly a fifth in Finnish specialist services. Possible explanations to our findings include changes in help-seeking, referrals and psychiatric problems, and delayed service access.